Developing Game-Based Animated Video Media to Increase Students’ Learning Interest in Fundamental Skills Movement - I Putu Eka Resdita; Guntur (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aims to develop animated video-based game learning media to increase students' interest in learning Physical Education and Health, especially in the material of basic movement skills at SDN 3 Kintamani. The study was conducted as Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The sample in this study comprised 20 third-grade students at SDN 3 Kintamani, selected using a total sampling technique. Meanwhile, one teacher and three experts were recruited as research subjects using purposive sampling. Data were collected through observation interviews, document analysis, and tests. The research instruments included: observation sheets, interview guides, document notes, and questionnaires. The collected data were analyzed using qualitative descriptive, quantitative descriptive, and paired-samples t-test. The results showed that animated video-based games are highly effective in increasing students' interest in learning, thereby classifying them as effective learning media. This is supported by the difference in mean scores between the pre-test and post-test. The mean score on the pre-test is 65.70, while the post-test achieves a higher mean of 86.45. The effect size was 3.649, categorized as a very large effect. This implies that animated video-based games strengthen game-based learning models and technology integration in learning basic movement skills